Correlation between mobility enhancement and conformational change in polyaniline and its derivatives: polaron lattice formation - Harima, Yutaka; Ogawa, Fumiyuki; Patil, Rahul; Jiang, Xiaoqing (Electrochimica Acta, 2007)
Conformational changes in polyaniline, poly(methyl aniline), and poly(methoxyaniline) are studied in perchloric acid and acetonitrile by means of an in situ reflection technique with oxidation level as a parameter. Stretching of polymer chains leading to enhancement of specular reflection at the polymer-coated electrodes is found to be well correlated with the increase in carrier mobility. The concomitant change in mobility and chain conformation observed with the polyaniline family is explained in terms of the formation of polaron lattice at increased oxidation levels. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Conformation; polyaniline; reflection; scattering : mobility